FACTORS RELATING TO EFL WRITERS’ DISCOURSE LEVEL REVISION SKILLS’ - Kobayashi, Hiroe; Rinnert, Carol (International Journal of English Studies, 2001)
This study investigated discourse level revising skills among three groups of Japanese EFL writers and the relationship between these skills and the two factors of English proficiency and writing experience. The three groups of university students (N = 53) differed in terms of their educational level and the amount of writing instruction they had received. Group 1, undergraduates with no writing instruction; Group 2, undergraduates with one year of English writing instruction; and Group 3, graduate students, were asked to revise English texts containing coherence problems at three discourse levels: intersentential, paragraph, and essay. The results showed that at the essay level, Group 2 outperformed Group 1, demonstrating revision skill close to that of Group 3, whereas Group 3 outperformed the other two groups overall, particularly at the intersentential level. While English proficiency and writing experience were both significantly related to revision performance, English proficiency was most strongly related to revision at the intersentential level. The results also imply that explicit instruction played an active role in students’ essay level revisions and use of correction strategies.